An Astonishing Extrarenal Wilms Localisation; Spinal Cord - TOKUÇ, AYŞE GÜLNUR; BOZKURT, SÜHEYLA; KAÇAR, KADRİYE EBRU; EKER, NURŞAH; SAKAR, MUSTAFA (My University, 2022)
Wilms\" tumour is a renal tumour mostly seen during the first 5 years of life and it accounts for 95% of renal malignancies during childhood. Its origin is primitive metanephric cells and, very rarely, it may occur in places other than the kidneys. The estimated rate of nephroblastoma outside the kidneys is approximately 0.5 to 1% of Wilms\" tumour cases. In this article, we report on a 3-year-old female patient who first presented with spinal dysraphism and a mass in the lumbar spinal cord with a histopathological diagnosis of nephrogenic rest, and after one year, a Wilms tumour arose in this location. This is a very rare extrarenal Wilms\" tumour location. Here, we report on a case with immature renal cells located in the lumber spinal cord associated with spinal dysraphism and the development of Wilms\" tumour there after one year.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; Children; Extrarenal; Wilms; TUMOR; TERATOMA; TISSUE